THE INFLUENCE OF THE STORAGE TEMPERATURE ON THE ACTIVITY OF THE RECONSTITUTED ORAL AMPICILLIN SUSPENSIONS - Yousif, Mirghani Abd Elrahman; Farouk, Asim (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
The following sets of experiments were conducted to investigate the extent of degradation of ampicillin antibiotic in suspension formulations stored at two different temperatures. The only variable in these experiments was the storage temperature. Oral ampicillin powders were reconstituted with distilled water and stored at two different temperatures of 5 o and 35 o C respectively representing the refrigeration and average room temperature in Sudan. The reconstituted ampicillin suspensions were assayed for initial drug contents, and then daily for a period of seven days in order to determine the effect of the storage temperature on the stability of reconstituted oral ampicillin suspensions. The drug contents in the different samples were determined using the microbiological cup plate method and the chemical spectrophotometric technique. The results obtained showed a remarkable decrease in the activity of the oral ampicillin suspensions stored at room temperature, when compared with the refrigerated ones. Recommendation of a unit-dose sachet package of ampicillin oral powder to be reconstituted at the time of intake was suggested.